Динамика частоты сердечных сокращений как показатель утомления обучающихся младшего звена общеобразовательной школы - Chernitsyna N. V. (Pedagogics and psychology: relevant theoretical and practical questions, 2016)
the estimation of fatigue school Junior level on the dynamics of heart rate during the training day of the week. The dependence of the frequency of heartbeats on the duration of training sessions, training in the first or second shift of the day of the school week.
Keywords: частота сердечных сокращений; утомление; младшее звено общеобразовательной школы; heart rate; fatigue; the lower level of General education school